2009
DOI: 10.1080/15389580903321727
|View full text |Cite
|
Sign up to set email alerts
|

Unlicensed Driving Among Urban and Rural Māori Drivers: New Zealand Drivers Study

Abstract: Driving before obtaining a driver's license was common practice and the amount of driving extensive, for both rural and urban drivers. Furthermore, contrary to common perceptions in New Zealand, the need and opportunities for driving were similar, irrespective of place of residence. This suggests that similar issues may need to be addressed by both urban and rural Maori community road safety providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
2
9
2
Order By: Relevance
“…The high probability of licensed drivers engaging in right-of-way violations could be explained by the fact that unlicensed drivers become “prudent drivers” in the streets because, in many countries, if the driver is cited for driving without a valid driving license, they may be fined, barred from obtaining a valid driving license for a period of time or incarcerated. Indeed, as reported by [ 56 , 57 ], drivers on roads or highways are more likely to be unlicensed than drivers on streets because on rural roads and highways, less public transport and taxi services are available and, considering the long distances, the likelihood of the unlicensed driver encountering the police is slim.…”
Section: Discussionmentioning
confidence: 99%
“…The high probability of licensed drivers engaging in right-of-way violations could be explained by the fact that unlicensed drivers become “prudent drivers” in the streets because, in many countries, if the driver is cited for driving without a valid driving license, they may be fined, barred from obtaining a valid driving license for a period of time or incarcerated. Indeed, as reported by [ 56 , 57 ], drivers on roads or highways are more likely to be unlicensed than drivers on streets because on rural roads and highways, less public transport and taxi services are available and, considering the long distances, the likelihood of the unlicensed driver encountering the police is slim.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-Licence driving has also been examined in surveys of novices who subsequently obtained a licence. Half of New Zealand's indigenous Maori population (McDowell et al 2009) and 12% of Los Angeles high school students were found to engage in pre-Licence driving (Carlos et al 2009). In addition, pre-Licence drivers have been found to have greater sensation seeking propensity (Begg et al 2010;Senserrick et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…e driver's individual characteristics can be analyzed from physiological and psychological factors, for example, the driver's age, gender and driving age, fatigue and emotions while driving, the driver's own driving style and safety attitude, traffic regulations awareness level, and so on. ese research studies show that [29][30][31] (1) the reaction speed to the emergency situation will be significantly reduced with age;…”
Section: Driving Characteristics Analysismentioning
confidence: 99%